AL-QUR’AN DAN KEBENARAN ILMIAH: TEROPONG KAJIAN MODERN DALAM FILSAFAT DAN KEILMUAN - Passa, Muh. Mukmin; Muh. Mukmin Passa (EL-FIKR: Jurnal Aqidah dan Filsafat Islam, 2024)
The study of the Quran and its relationship with scientific truths has emerged as an intriguing topic in modern scholarly discourse. The Quran, revered as the sacred scripture of Islam, serves not only as a spiritual guide but also encompasses various aspects that resonate with contemporary scientific discoveries. This research aims to explore the interplay between the Quran and modern science within a philosophical framework. Employing an interdisciplinary approach, the study identifies scientific concepts within the Quran that correlate with current scientific findings and theories. The research method to be used in this study is a qualitative method. Qualitative methods were chosen because they are able to provide an in-depth understanding of complex phenomena, such as the relationship between the Qur'an and scientific truth. Thus, this paper reflects the complexity of the relationship between science and religion, particularly within the context of Islam and the Quran, emphasizing the importance of dialogue between science and religion in comprehending the truths about human existence. This exploration seeks to deepen our understanding of how religious texts like the Quran can enrich discussions on scientific discoveries, fostering a holistic approach to the complexities of reality. Keyword: Qur’an, Scientific Truth, Science.